Answer:
The proof is given below.
Explanation:
Given:
![f'(x)\leq 2,\ f(0)=4, \ x>0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3vgbgv42mm45btwlf2200cwf4oo7s869td.png)
Using Mean Value Theorem,
![f'(c)=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/gmtjx2z6e8t6hops48w2kkui28vv4kuaq5.png)
Here,
![a=0,\ b=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/h3wpgjtin8muqe3dx7tdba0igtzxo899mp.png)
Therefore,
![f'(c)=(f(x)-f(0))/(x-0)=(f(x)-4)/(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/claef3ewzucwd1892fdf8yco2x3d5h4e4h.png)
Now, as per question the derivative of
is less than or equal to 2.
Therefore,
. Plug in the value of
. This gives,
![(f(x)-4)/(x)\leq 2\\f(x)-4\leq 2x ...............(\textrm{Cross product})\\f(x)\leq 2x+4 ..............(\textrm{Adding 4 both sides})](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3p7axka1c9bcdz5v760v0bg5auwef4cmaz.png)
Therefore, we get,
and hence it is proved using mean value theorem.